1997
DOI: 10.1111/j.1348-0421.1997.tb01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Curdlan Sulfate in the Binding of HIV‐1 gp120 to CD4 Molecules and the Production of gp120‐Mediated TNF‐α

Abstract: To clarify the mechanism by which curdlan sulfate (CRDS) inhibits human immunodeficiency virus (HIV)-1 infection, we examined its influence on the binding of gp120 to CD4 molecules on T cells and macrophages, as well as on the production of TNF-a by gp120-stimulated macrophages (which promotes HIV-1 replication). CRDS treatment of cells not only inhibited the binding of HIV-1 gp120 to CD4+ cells, but also inhibited TNF-a production induced by gp120. Inhibition of HIV-1 infection by CRDS may be related to these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…(29) A second wave of cytokine secretion in mixed cultures was preceded by the infection of placental macrophages with HIV-1. Several studies have shown that both the envelope glycoproteins and the Tat protein of HIV-1 can induce production of IL-1b, (52,53) IL-6, (54,55) and TNF-a (56,57) by signal transduction via the CD4 cell surface receptor and transactivation of cytokine gene promoters, respectively. Obviously, IL-1b, IL-6, and TNF-a secreted by HIV-1-infected macrophages may further increase the rate of virus production in HIV-1-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…(29) A second wave of cytokine secretion in mixed cultures was preceded by the infection of placental macrophages with HIV-1. Several studies have shown that both the envelope glycoproteins and the Tat protein of HIV-1 can induce production of IL-1b, (52,53) IL-6, (54,55) and TNF-a (56,57) by signal transduction via the CD4 cell surface receptor and transactivation of cytokine gene promoters, respectively. Obviously, IL-1b, IL-6, and TNF-a secreted by HIV-1-infected macrophages may further increase the rate of virus production in HIV-1-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gpl20 can induce several kinds of immune dysfunction observed in HIV-1-infected patients such as CD4 down-modulation on T cells, T-cell activation, and T-cell anergy (shown as human leukocyte antigen [HLA]-class II molecule expression on T cells, low production of mitogen-induced interleukin [IL]-2, and a weak response in the mixed lymphocyte reaction), polyclonal B-cell activation, and apoptotic death of CD4+ T cells (5,7,14,23,26,28,36,41,43,44). These immune abnormalities have been reported to be mediated by several cytokines, such as tumor necrosis factor (TNF)-a, IL-6, and IL-10 produced from gpl20-stimulated macrophages (7,23,26,28,36,41,43,44,46), and to be mediated by phosphorylation of protein tyrosine kinase p56lck in CD4+ cells induced by binding of HIV-1 envelope glycoprotein (19,21). Although such immunologie changes are seen with HIV-2 infection, they are less severe than would be expected with HIV-1 infection in similar crosssectional settings (29).…”
Section: Hiv Envelope Glycoproteinmentioning
confidence: 99%
“…Curdlan has been reported to be a useful additive for a variety of food products, such as for yogurt stability improvement [5], noodles, sauces, frozen foods and packaged meats for texture improvement and stabilizing ability [6]. Curdlan and its derivatives have also been used as drug delivery vehicles [7] and for sustained release of drugs [8]. Curdlan sulfates has been shown to exhibit high anti-AIDS activity [9, 10] and strong inhibitory action on blood coagulation and hence can be used for the treatment of thrombosis [11].…”
Section: Introductionmentioning
confidence: 99%